PTU-149 Cambridge-Miami risk assessment for intestinal transplantation. (28th May 2012) - Pither, C; Sivaprakasam, R; Takahashi, H; Nishida, S; Butler, A; Moon, J; Dawwas, M D; Gabe, S; Jamieson, N; Woodward, J; Island, E; Tzakis, A; et al.
Abstract : Introduction: The Cambridge-Miami (CaMi) preoperative risk assessment score has been previously validated in a small cohort and accurately predicted the survival after intestinal transplantation. We undertook a further validation in a larger cohort of patients. Methods: Co-morbidity and lost venous access are used as putative preoperative risk factors, each scored 0–3 for severity. Patients (72 adults (M:F, 33:39) received an isolated intesinal graft (27), or a cluster graft including intestine (45). Results: Mean (SD) survival was 1501 (1444) days. The Kaplan–Meier analysis of survival revealed a significant inverse association between survival and CaMi score [logrank test for trend, p<0.0001]. Patients were grouped into CaMi scores of 0 and 1, 2 and 3, 4 and 5, 6 and above, and HR [95% CIs] for death (compared to group 0+1) was found to increase as the CaMi score increased; 1.945 [0.7622 to 5.816], 5.075 [3.314 to 36.17] and 13.77 [463.3 to 120100] respectively and was significantly greater than group 0+1 at group 4+5 (p<0.0001). Conclusion: The ability to predict survival from the CaMi score might allow better patient selection, and identify patients for earlier transplantation. Competing interests: None declared.